Detection of Human Papilloma Virus in Colorectal Cancer by Polymerase Chain Reaction Technique in A Tertiary Care Hospital of Bangladesh - Das, Narayan Chandra; Hossain, Mohammad Ismail; Nasreen, Saida; Nasreen, Mehnaz; Bhattacharjee, Pradip; Rahman, Zillur (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: Human Papilloma Virus (HPV) infection is associated with the development of several cancers, including oral, esophageal, skin, lung, and uterine cervix. Association of HPV and colorectal cancers remains controversial. The aim of this study was to evaluate the association between HPV infection and colorectal cancer in Chattogram of Bangladesh. Materials and methods: The study was carried out in the Department of Pathology, Chattogram Medical College, Bangladesh over a period of one year from July, 2013 to June, 2014. A total of 60 cases were included in the study during the time period. Histopathological type and grading was done. HPV type 16 and 18 DNA was examined from all samples by means of Real Time PCR using type specific primer named E7 protein. Finally association between HPV types 16/18 with colorectal carcinoma was assessed by Chi-square (c2) test. Results: The mean age of 60 patients was 45.35 years (Range 17-75 years). Rectum was the common site of tumour 26 (43.3%). HPV type 16 and 18 was detected in 25 (41.7%) cases, out of whom 24 (96%) were associated with HPV16, and only one case was both HPV type 16 and 18. As regarding histological type, out of 25 cases 21 (84%) cases of adenocarcinoma, 3 (12%) case of signet ring carcinoma and only 1 (1.6%) case of mucinous carcinoma were positive for HPV. Conclusion: HPV specially subtype 16, may play a role in the oncogenesis of Colorectal Carcinoma. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 44-48